If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -3) = 2x + -5 Reorder the terms: 3(-3 + 4x) = 2x + -5 (-3 * 3 + 4x * 3) = 2x + -5 (-9 + 12x) = 2x + -5 Reorder the terms: -9 + 12x = -5 + 2x Solving -9 + 12x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -9 + 12x + -2x = -5 + 2x + -2x Combine like terms: 12x + -2x = 10x -9 + 10x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 -9 + 10x = -5 + 0 -9 + 10x = -5 Add '9' to each side of the equation. -9 + 9 + 10x = -5 + 9 Combine like terms: -9 + 9 = 0 0 + 10x = -5 + 9 10x = -5 + 9 Combine like terms: -5 + 9 = 4 10x = 4 Divide each side by '10'. x = 0.4 Simplifying x = 0.4
| 0=x^2+8x+4 | | 4s+-8=16 | | 7x-3y=3 | | .5x+1.15=1.65 | | 1x-2x=20 | | r+2=5r+6 | | x(2)+4x=12 | | x(2)+6x=-8 | | 2v+18=16-4(v-7) | | x^3+8x^2+21x+8=0 | | 9x^3+8x^2+18x+12=0 | | 2x+8=18 | | 8h+4=3h-4 | | x^4+8x^3+21x^2+18x=0 | | (x+y)2=x+xy+y | | 14(t-2)+7t=7(3t+5)-13 | | 49=30-k/16 | | 4x+6y=21 | | 4x-1=2+X | | (2x-5y)-(2x+5y)= | | X^3-21x+10=0 | | x^2+20x+90=0 | | 10+x-1/3=0 | | -64x^2+176x-121=0 | | (w^2)-w=36+4w | | (c^2)=16 | | 39.6=5.5l | | x/3-1.2=-1.566 | | -11=4-4x | | 3(7x-21)=-14 | | 9x+7=2(3x+8) | | -9y=-117 |